Effects of biperiden and acute tryptophan depletion and their combination on verbal word memory and EEG - Borghans, Laura G. J. M. (Psychopharmacology (Berl), 2017)
BACKGROUND: Research on the neurobiological foundations of memory has shown that multiple neurotransmitters play an important role in memory processing. To study the interaction between neurotransmitters such as acetylcholine and serotonin, pharmacological models can be used. In this study, we tested the effects of the muscarinic M1 antagonist biperiden, acute tryptophan depletion (ATD), and the interaction between the two on episodic memory using the verbal learning task. METHODS: The study was conducted according to a double-blind, placebo-controlled, four-way crossover design. Seventeen participants received biperiden (2.0 mg), ATD (SolugelP), a combination of both, or a placebo in counterbalanced order with a wash out of at least 7 days. A verbal learning task was performed while recording electroencephalography. The task consisted of an immediate and delayed recall as well as a recognition part. RESULTS: Results revealed decreased scores on the delayed recall after biperiden and ATD separately but no significant interaction between the two. However, the event-related potential components P3b, N400, and P600 did show an interaction during encoding. CONCLUSION: These results indicate that both BIP and ATD impair episodic memory. However, an interaction between the serotonergic and cholinergic system on memory performance is not supported.